Answer:
We conclude that the following statements can be proved such as:
Explanation:
Given the expression
![p = 2q+1](https://img.qammunity.org/2022/formulas/mathematics/high-school/bbzbfzlik9oqbph4fl51ntxd04mc3fdois.png)
Given
![p = 8](https://img.qammunity.org/2022/formulas/mathematics/high-school/7mijz3yzdmzbtimear8hfqp2ae4jqh5kjo.png)
IF WE SUBSTITUTE p=2q+1 in p=8
Now, substituting p = 2q+1 in the expression p=8
![p = 8](https://img.qammunity.org/2022/formulas/mathematics/high-school/7mijz3yzdmzbtimear8hfqp2ae4jqh5kjo.png)
∵ p = 2q+1
Therefore, we conclude that the following statements can be proved such as: